Online Version of the Self-Administered Food Frequency Questionnaire for the Iranian Adult Population - Mehrnaz Morvaridi; Majid Karandish; Hadi Bazyar; Hamid Rasekhi; Hossein Bavi Behbahani (Nutrition and Metabolic Insights)
Background: With the growing accessibility of the internet, dietary assessment tools, including food frequency questionnaires (FFQs), are increasingly being adapted for web platforms. A web-based FFQ was developed as a dietary assessment tool for healthy adults in Iran. Objective: This study aimed to develop an online FFQ for dietary data collection among Iranian adults and to compare its performance with the validated Iranian printed FFQ. Methods: Eligible participants were randomly assigned to complete both the printed and web-based FFQs. The type of FFQ alternated for each participant after 10 days. The agreement between the two FFQs was assessed using the Bland-Altman method and correlation analysis. Results: Of the 190 participants, final analyses were conducted on 141 individuals, including 70 females (49.6%) and 71 males (50.4%) who completed both FFQs. Agreement was high for all nutrient intakes ( r  > .8). Among food groups, “Whole grains” showed the highest correlation ( r  = .84), while “Potato” had the lowest ( r  = .25). There were no significant differences in the time taken to complete the questionnaires. Conclusion: The web-based FFQ demonstrated strong agreement with the validated printed FFQ, accurately reflecting nutrient and food group intakes in Iranian adults.